A study of association between vitamin d deficiency in sepsis - Ahmed, Nishat; Yadav, Vikram; Soni, Rajendra Kumar; Nagaraj, Niranjan; Berwal, Pramod Kumar; Sengar, Gunshyam Singh (International Journal of Contemporary Pediatrics, 2016)
Background:Vitamin D is a fat-soluble steroid hormone that contributes to the maintenance of normal calcium homeostasis and skeletal mineralization the aims of this study is to evaluate vitamin D levels in pediatric patients admitted in the intensive care unit with sepsis. Methods: Fifty children between 1 year to 12 years of age with systemic inflammatory response syndrome (SIRS) with suspected or proven sepsis, admitted in PICU were included for the study. Blood was drawn at the time of admission on the first day of hospital stay for measurement of 25-hydroxyvitamin D (25-OHD) levels. Results:Forty two (84%) patients out of 50 patients had vitamin D levels < 30ng/ml and only 8 patients had vitamin D >30 ng/ml. This was statistically significant as the p value was <0.05. Conclusions:Lower 25-OHD levels are associated with sepsis. The multiple functions of vitamin D in the immune system’s response to infection suggest it may be an integral component in combating sepsis.